Efficacy of Early Prophylaxis Against Catheter-Associated Thrombosis in Critically Ill Children: A Bayesian Phase 2b Randomized Clinical Trial*. Issue 3 (18th December 2020) - Faustino, E. Vincent S.; Shabanova, Veronika; Raffini, Leslie J.; Kandil, Sarah B.; Li, Simon; Pinto, Matthew G.; Cholette, Jill M.; Hanson, Sheila J.; Nellis, Marianne E.; Silva, Cicero T.; Chima, Ranjit; Sharathkumar, Anjali; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : OBJECTIVES: We obtained preliminary evidence on the efficacy of early prophylaxis on the risk of central venous catheter-associated deep venous thrombosis and its effect on thrombin generation in critically ill children. DESIGN: Bayesian phase 2b randomized clinical trial. SETTING: Seven PICUs. PATIENTS: Children less than 18 years old with a newly inserted central venous catheter and at low risk of bleeding. Intervention: Enoxaparin adjusted to anti-Xa level of 0.2–0.5 international units/mL started at less than 24 hours after insertion of central venous catheter (enoxaparin arm) versus usual care without placebo (usual care arm). MEASUREMENTS AND MAIN RESULTS: At the interim analysis, the proportion of central venous catheter-associated deep venous thrombosis on ultrasonography in the usual care arm, which was 54.2% of 24 children, was significantly higher than that previously reported. This resulted in misspecification of the preapproved Bayesian analysis, reversal of direction of treatment effect, and early termination of the randomized clinical trial. Nevertheless, with 30.4% of 23 children with central venous catheter-associated deep venous thrombosis on ultrasonography in the enoxaparin arm, risk ratio of central venous catheter-associated deep venous thrombosis was 0.55 (95% credible interval, 0.24–1.11). Including children without ultrasonography, clinically relevant central venous catheter-associated deep venous thrombosis developed in one of 27 children (3.7%) in the enoxaparin arm and seven of 24 (29.2%) in the usual care arm ( p = 0.02). Clinically relevant bleeding developed in one child randomized to the enoxaparin arm. Response profile of endogenous thrombin potential, a measure of thrombin generation, was not statistically different between trial arms. CONCLUSIONS: These findings suggest the efficacy and safety of early prophylaxis that should be validated in a pivotal randomized clinical trial.